2019
DOI: 10.2174/1874210601913010171
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of the Prevalence of Periodontitis in Saudi Arabia: A Proposal for a National Oral Health Research Agenda for Vision 2030

Abstract: Objective:The objective of this narrative review is to summarize the current knowledge on the prevalence of periodontitis in the Kingdom of Saudi Arabia (KSA) and to make recommendations for monitoring and improving oral health in the KSA population.Background:Periodontitis is a significant health issue in the general population, so conducting routine public health surveillance for this condition is important in every country. KSA is currently implementing a strategic plan called Vision 2030 which aims to impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Similarly, poor periodontal health is also a significant oral health problem among adults in the country. A recent review reported a lack of periodontal health in 50% of the adult population in Saudi Arabia and showed a strong association with diabetes and tobacco use [32]. In addition, the existence of a strong bidirectional relationship between periodontal disease and diabetes can further worsen oral and systemic health [33].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, poor periodontal health is also a significant oral health problem among adults in the country. A recent review reported a lack of periodontal health in 50% of the adult population in Saudi Arabia and showed a strong association with diabetes and tobacco use [32]. In addition, the existence of a strong bidirectional relationship between periodontal disease and diabetes can further worsen oral and systemic health [33].…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent review, the contemporary information on the prevalence of PD and associated risk factors in the Kingdom of Saudi Arabia (KSA) is deficient ( Alshammari et al, 2019 ). It was emphasized by the Saudi national oral health research program that, according to Vision 2030, there is a substantial need to conduct more research related to oral health conditions in the KSA.…”
Section: Introductionmentioning
confidence: 99%
“…There is a lack of recent data regarding the prevalence of PD among the Saudi population ( Alshammari and Wahi, 2019 ). Few studies suggest that the rates of oral health conditions are high; however, these findings are very general, and more studies must be performed to assess the prevalence of the PD in particular ( Claffey et al, 1990 , Idrees et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%